Identification and Peptidomic Profiling of Exosomes in Preterm Human Milk: Insights Into Necrotizing Enterocolitis Prevention. Issue 13 (14th May 2019) - Wang, Xingyun; Yan, Xiangyun; Zhang, Le; Cai, Jinyang; Zhou, Yahui; Liu, Heng; Hu, Yin; Chen, Wenjuan; Xu, Siliang; Liu, Peipei; Chen, Ting; Zhang, Jun; et al.
Abstract : Scope: Human breast milk has been shown to prevent necrotizing enterocolitis (NEC). Although exosomes have been identified in breast milk, their function and components have not been fully addressed. This study is conducted to elucidate the differences in peptidomic complexities between preterm and term milk exosomes. Methods and results: Breast milk samples are collected from healthy lactating mothers who have delivered term and preterm infants. Exosomes are separated and quantified. The protective effects of purified exosomes against NEC are investigated both in vitro and in vivo. The peptidomic complexities in term and preterm milk exosomes are analyzed by iTRAQ LC‐MS/MS to screen differentially expressed exosomal peptides. Preterm milk exosomes administration significantly enhances proliferation and migration of intestinal epithelial cells compared with term milk exosomes. A total of 70 peptides are found to be significantly modulated in preterm milk samples compared to term milk samples. Of these, 47 peptides are upregulated, and 23 peptides are downregulated. Bioinformatics analysis suggests several potential regulatory roles of the altered peptides in intestinal epithelial cell function. Conclusion: These results reveal the differences for the first time in peptidomic complexities between preterm and term milk exosomes. Milk exosome administration might be a promising prevention for NEC. Abstract : This study is the first report on the different peptidomic profiles between term and preterm milk exosomes. The peptides highly enriched in preterm milk exosomes may possess protective activities against necrotizing enterocolitis (NEC) by promoting intestinal cell proliferation and migration.